Identify the Ingredients in Kombucha, Which is Safe for Magh and Gerd Sufferers - Misahradarsi Dongoran (Bioedunis Journal, 2023)
Kombucha tea is a fermented drink which usually has a tea base. It is made from Kombucha starter culture (mushroom/scoby) tea with added sugar, and Kombucha from the previous bath (starter tea) which is the basic ingredient for making this kombucha tea. The taste of Kombucha itself is acidic, but the level of acidity depends on how long the fermentation takes. This research was conducted using a qualitative descriptive method, with data collection and analysis carried out first, both written and verbal. In the midst of public anxiety, people don't know that the acid contained in kombucha does not have a bad influence on people with Magh and Gerd, especially, Kombucha contains various vitamins, including organic acid, acetic acid, 4-ethylphenol, ethyl acetate, antioxidants, Vitamins B and C. After research and analysis, it can be concluded that the substances contained in Kombucha tea are not dangerous for Magh and Gerd sufferers, on the contrary, Kombucha is one of the medicinal drinks consumed by Magh and Gerd sufferers.